Insecticidal Activity Seed Extract of Cerbera sp. against Helopeltis antonii Sign (Hemiptera; Miridae) - Herianto, Herianto; Syahputra, Edy; Ramadhan, Tris Haris (Jurnal Sains Mahasiswa Pertanian, 2015)
The objectives of this study were evaluated the insecticidal activity ethanol seed extract of Cerbera sp. on mortality and reproduction H. antonii. The bioassays were conducted using residuel methods. Observations on insect mortality conducted every 24 hours for 8 days. Relationship between concentrations and mortality was analyzed by probit. The number of offspring emerged from adult female  analyzed by ANOVA. The result shows that Cerbera sp. seed extract possessed insecticidal activity against H. antonii with LC₅₀ of 0.32%. In the reproduction test, LC₂₅, LC₅₀ and LC₇₅ inhibit reproduction of H. antoni adult. Keywords : Cerbera sp., Helopeltis antonii, insecticide botanical